2001
DOI: 10.1038/sj.cr.7290092
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated transformation and assessment of factors influencing transgene expression in loblolly pine (Pinus taeda L.)

Abstract: This investigation reports a protocol for transfer and expression of foreign chimeric genes in loblolly pine (Pinus taeda L.). Transformation was achieved by co-cultivation of mature zygotic embryos with Agrobacterium tumefaciens strain LBA4404 which harbored a binary vector (pBI121) including genes for b-glucuronidase (GUS) and neomycin phosphotransferase (NPTII). Factors influencing transgene expression including seed sources of loblolly pine, concentration of bacteria, and the wounding procedures of target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
(23 reference statements)
2
9
0
Order By: Relevance
“…It was reported that the initial culture on the medium without antibiotic promoted active proliferation of cultures of Pinus strobus L. (Levée et al 1999), Picea abies (Klimaszewska et al 2001) and Pinus taeda (Tang 2001). One week after culture on the selection medium, the transformed cells started to regenerate.…”
Section: Resultsmentioning
confidence: 96%
“…It was reported that the initial culture on the medium without antibiotic promoted active proliferation of cultures of Pinus strobus L. (Levée et al 1999), Picea abies (Klimaszewska et al 2001) and Pinus taeda (Tang 2001). One week after culture on the selection medium, the transformed cells started to regenerate.…”
Section: Resultsmentioning
confidence: 96%
“…Ninety transgenic plants were regenerated from hygromycinresistant calli derived from families WO3, 8-1082 and 11-1029, and 19 transgenic plantlets were established in soil. The presence of the uidA gene in the plant genome was confirmed by polymerase chain reaction, Southern blot, and plant DNA/T-DNA junction analysis (Tang 2001;Tang et al 2001).…”
Section: Regeneration Of Transgenic Plantsmentioning
confidence: 99%
“…It would have been easier to determine false positive results, if the vector sequence contained marker genes from more than one organism. However, pBI121 is a popular binary vector and has recently been used by researchers for several plants including peanut (Rohini and Rao 2001;Sharma and Anjaiah 2000), shallot (Zheng et al 2001), spruce (Le et al 2001), buckwheat (Kojima et al 2000), poppy (Park and Facchini 2000) and pine (Tang 2001). pBI121 has also been used for in planta transformation of cactus (Seol et al 2008).…”
Section: Discussionmentioning
confidence: 98%